Cross-functional HRM and Marketing Collaboration in Driving Consumer Needs-based Eco-Friendly Product Innovation - Mardikaningsih, Rahayu; Essa, Nabeela Ebrahem (Metromedia, 2025)
The development of environmentally friendly products has increasingly become a strategic priority in modern business, driven by the growing consumer awareness of sustainability issues. This study examines the role of cross-functional collaboration between Human Resource Management (HRM) and marketing in supporting the creation of green products that are relevant to consumer needs. The discussion begins by tracing general and specific phenomena, followed by an identification of principal issues such as divergent objectives, communication barriers, resource allocation constraints, cultural resistance, and external pressures that undermine the effectiveness of collaboration. Through a literature review approach, the study reveals that the synergy between HRM and marketing holds significant potential to generate competitive added value. HRM supports this process by developing green competencies, promoting a sustainable work culture, and providing incentives that drive innovation, while marketing contributes through mapping consumer needs and designing market strategies aligned with sustainability trends. However, the success of this synergy depends highly on organization’s preparedness to overcome structural, cultural, and regulatory obstacles. In conclusion, strong cross-functional collaboration is underlined by robust performance indicators, enhanced green workforce competencies, and the strategic alignment of HRM marketing. In turn, such collaboration not only enhances organizational competitiveness but also supports the broader agenda of global sustainability